Відповідь:(-1,2)² = (1,2)² = 1,2 * 1,2 = 1,44
(-1,2)³ = -1,2 * (-1,2) * (-1,2) = -1,2 * 1,2 * 1,2 = - 1,44 * 1,2 = -1,728
Покрокове пояснення:
Ответ:
1.44: -1.728
Пошаговое объяснение:
-1.2²=-1.2*-1.2=1.44
-1.2*-1.2*-1.2=-1.728
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:(-1,2)² = (1,2)² = 1,2 * 1,2 = 1,44
(-1,2)³ = -1,2 * (-1,2) * (-1,2) = -1,2 * 1,2 * 1,2 = - 1,44 * 1,2 = -1,728
Покрокове пояснення:
Ответ:
1.44: -1.728
Пошаговое объяснение:
-1.2²=-1.2*-1.2=1.44
-1.2*-1.2*-1.2=-1.728